2019
DOI: 10.1007/s00348-019-2690-9
|View full text |Cite
|
Sign up to set email alerts
|

On the subsonic near-wake of a space launcher configuration without jet

Abstract: Wake flows have been extensively investigated in the past mainly with the objective to reduce drag. The failure of Ariane 5 Flight 157 though revealed that the understanding has not been sufficient, which triggered a new series of base-flow investigations. Most of them scrutinized the dynamics of the flow at one specific point along the flight path either in the subsonic, transonic, or supersonic range. However, no coherent image of the flow topology development in terms of a parametric study is available so f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…The current study has the objective to contribute insights into the velocity field and Reynolds stress distribution over a wide subsonic range from Mach 0.5 to 0.9. The work is an extension of a preceding investigation on the exact same configuration without exhaust jet (Saile et al 2019). That study found a similar velocity and Reynolds stress distribution for the investigated flow range independently of the Mach and Reynolds number if scaled with the shear layer reattachment length.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…The current study has the objective to contribute insights into the velocity field and Reynolds stress distribution over a wide subsonic range from Mach 0.5 to 0.9. The work is an extension of a preceding investigation on the exact same configuration without exhaust jet (Saile et al 2019). That study found a similar velocity and Reynolds stress distribution for the investigated flow range independently of the Mach and Reynolds number if scaled with the shear layer reattachment length.…”
Section: Introductionsupporting
confidence: 61%
“…The most dominant influence was found in the fluctuations, which are influenced by the merging shear layers from the wind tunnel nozzle and wind tunnel model. However, in the predecessor study of the current series (Saile et al 2019), this effect appeared negligible for the current experimental setup. This was attributed to the comparably large diameter ratio between the wind tunnel nozzle and the base of the model.…”
Section: Methodsmentioning
confidence: 70%
See 3 more Smart Citations